Physicochemical characterization and bioactive compounds in breadfruit (Artocarpus altilis) and its dried products. (Research, Society and Development, 2021)
Breadfruit (Artocarpus altilis) is described as an important food source in the diet of several countries, being considered as a valuable food with the potential to positively impact food security in the world. Breadfruit is a fruit of Asian origin with considerable economic and food importance for the region, due to its exceptional nutritional characteristics that bring benefits to the health to its consumers. However in Brazil, the fruit is little known and is underused. Only a very few scientific publications emphasizing the technological characteristics of breadfruit processing have been reported in the literature, which motivated the realization of the present research on its physicochemical characteristics. The fruits used were obtained from domestic orchards at the ripe and “green” ripening stages. The analyses performed were of pH, total soluble solids, total titratable acidity, water activity, ash content, lipids, protein, moisture and color (L*, a*, b*, C* and ºHue). Antioxidant activity through ABTS, DPPH and FRAP assays, and total phenolics and flavonoids compounds were determined. Descriptive data were analyzed by Analysis of Variance (ANOVA), Tukey mean test (p